Prediction of Stock Market Instability Based on MS-VAR Model. Issue 4 (March 2021) - Lai, Yujie; Hu, Yibo
Abstract: Prediction model is established further in this essay based on the basic filtering procedure of state-space model with Markov zone conversion to predict the dynamic predicted value and total predicted value of the system variables in the future sixty stages and to predict the zone conversion probability of the system. The prediction results show that the monetary policy action mechanism of the system varies in different processes of zone conversion.